The role of the diastolic stress echocardiographic test in the diagnosis of heart failure with preserved left ventricular ejection fraction - Bošković Nikola; Dedić Srđan; Đorđević Ana; Giga Vojislav (Medicinski Glasnik Specijalne Bolnice za Bolesti Štitaste Žlezde i Bolesti Metabolizma "Zlatibor", 2023)
We present the case of a 68-year-old female patient with exertional dyspnea, mild pretibial oedema and echocardiographically verified enlarged left atrium, but with preserved left ventricular systolic function and normal left ventricular filling pressures at rest. NT-proBNP values were within reference values. The diastolic stress echocardiographic test confirms the presence of heart failure with preserved ejection fraction (HFpEF). This case report represents the complexity of diagnosing HFpEF in everyday clinical practice.